NUTRITIONAL ANALYSIS OF SOME SELECTED WILD EDIBLE SPECIES CONSUMED BY THE BODO TRIBES OF KOKRAJHAR DISTRICT, BTC, ASSAM; INDIA - Brahma, Jahnovi; SINGH, B.; RETHY, P; GAJUREL, P (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Abstract- The paper deals with the native uses of ethno botanical species, identification and chemical analysis of some selected wild edible plants consumed by the Bodo tribes inhabiting various areas of Kokrajhar district. A total of one eighty-one wild edible plant species were identified and recorded of which ten species are chemically analyzed and presented in this paper. Evaluation of nutritional and bioactive compounds shows that the content of protein were in the range of 13.81 to 23.66% of dry weight, moisture content accounted for 81 to 94.5% of fresh weight; ash content 20 to 43% of dry weight; total solids of 11.5 to 19% in dry weight; carbohydrates content of 7.6 to 48.4% of dry weight and crude fat of 0.54 to 2.37% of dry weight. Results also revealed mineral composition in the range of Zn (0.245-10.96ppm), Mg (1.10-6.433ppm), Mo (1.18-6.58ppm), Cu (0.168-0.551ppm), Fe (15.97-27.44ppm) and Mn (0.424-3.488ppm). Comparing the nutritional contents with recommended dietary allowances (RDA), the results indicated that these wild edible plants could act as a good supplement for various nutrients like proteins, carbohydrates and micronutrients.